Does it pay to be a public-sector employee? - Fabien Postel-Vinay (IZA World of Labor, 2015)
Direct wage comparisons show that public-sector employees earn around 15% more than private-sector employees. But should these differences be interpreted as a “public-sector premium”? Two points need to be considered. First, the public and private sectors differ in the jobs they offer and the type of workers they employ, which explains a large share of the wage gap. Second, public- and private-sector careers also differ in other important dimensions, such as job stability and income progression, which are relevant to individual career choices. So any comparison of the two sectors should take these points into account.
Keywords: J45; J31; J62; 330; public-private pay gap; lifetime career values; inequality